Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1002/j.1551-8833.1983.tb05143.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of bacterial counts with turbidity and free chlorine in two distribution systems

Abstract: In this study, the diversity of organisms identified by using standard plate count (SPC) and membrane filtration strongly suggests an established microbial ecosystem in two distribution systems. The SPC exhibited no relationship with coliform count when the SPC was less than 50 organisms/mL. The SPC was not dependent on low‐level turbidity and varied with respect to free chlorine residuals. The frequency of coliform isolation was independent of turbidity and free chlorine. Specifically, encapsulated coliforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 19 publications
5
19
0
1
Order By: Relevance
“…b), which was higher than that of antibiotic‐sensitive E. coli (ATCC 25922). Previous studies reported that antibiotic‐resistant organisms could produce more capsular material than antibiotic‐sensitive strains (Reilly and Kippin ; Rusin and Gerba ). The production of capsule by antibiotic‐resistant organisms could be an important factor in delaying microbial self‐aggregates, contributing to a higher UV dose, which was necessary to enter the tailing phase and the low inactivation efficiency at the fast kinetics phase.…”
Section: Discussionmentioning
confidence: 98%
“…b), which was higher than that of antibiotic‐sensitive E. coli (ATCC 25922). Previous studies reported that antibiotic‐resistant organisms could produce more capsular material than antibiotic‐sensitive strains (Reilly and Kippin ; Rusin and Gerba ). The production of capsule by antibiotic‐resistant organisms could be an important factor in delaying microbial self‐aggregates, contributing to a higher UV dose, which was necessary to enter the tailing phase and the low inactivation efficiency at the fast kinetics phase.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, work by Goshko et al (1983) found positive correlations between HPCs and turbidities in the 0.83-8.89 NTU range. On the other hand, a study reported by Reilly and Kippin (1983) suggested that turbidity around 1.0 NTU does not affect the frequency with which either coliforms or HPC organisms occur in the analysis. Particulate matter (e.g., organic, inorganic, higher microorganisms) can protect bacteria and viruses from the effects of disinfection.…”
Section: Turbiditymentioning
confidence: 92%
“…Biofilms will grow on cast or ductile iron, cement or polyvinyl chloride and may include chlorine-sensitive bacteria because the diffusion of chlorine to the walls of the pipes is impeded by the film (Reilly & Kippin 1983;Chadderton et al 1992).…”
Section: Heterotrophic Plate Count (Hpc) Bacteria Removalmentioning
confidence: 98%